PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK DAN KEPERCAYAAN TERHADAP LOYALITAS PELANGGAN AROMANIA PARFUMERY DI KOTA BENGKULU - Sri Ekowati; Selamat Riyadi (Universitas Muhammadiyah Bengkulu, 2021)
ABSTRACTThis study aims to determine the effect of service quality, product quality andÂ trust on customer loyalty aromania parfumery Bengkulu. This type of research is a survey research with a quantitative approach, the object of this research is the consumers in Aromania parfumery, which is precisely located on Jl. Kapuas Raya, Lingkar Barat, Kec. Gading Cempaka, Bengkulu City. with the sampling method, namely non-propability technique, namely insidential sampling technique. The number of respondents in this study were 105 people. The data collection method used a questionnaire. By using data analysis techniques using Multiple Linear Regression Analysis Test, and Hypothesis Test, namely test t and test f. The results of this study can be concluded that the variable service quality Aromania parfumery has a positive effect on customer loyalty, product quality has a positive effect on customer loyalty, and trust has a positive effect on customer loyalty.Keywords: Service Quality, Product Quality, Customer Trust and Loyalty.